2017
DOI: 10.1016/j.jrurstud.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the socio-cultural contexts of fishers and fishing: Developing the concept of the ‘good fisher’

Abstract: The version presented here may differ from the published version. If citing, you are advised to consult the published version for pagination, volume/issue and date of publication 1 Exploring the socio-cultural contexts of fishers and fishing: developing the concept of the 'good fisher'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 60 publications
1
61
0
Order By: Relevance
“…,40Ð42], this paper utilises the conceptual framing of the 'good fisher' [18]. This framing is informed by Bourdieu's [36,43Ð45] notion of capital, field and habitus which provides a useful conceptual apparatus for attempting to understand the socio-cultural contexts of fishing and fishers as well as the temporal dimension of fishing lives.…”
Section: The 'Goodfisher'mentioning
confidence: 99%
See 4 more Smart Citations
“…,40Ð42], this paper utilises the conceptual framing of the 'good fisher' [18]. This framing is informed by Bourdieu's [36,43Ð45] notion of capital, field and habitus which provides a useful conceptual apparatus for attempting to understand the socio-cultural contexts of fishing and fishers as well as the temporal dimension of fishing lives.…”
Section: The 'Goodfisher'mentioning
confidence: 99%
“…Bourdieu [46] further breaks down cultural capital into three categories: institutional, objectified and embodied. Research found that symbolic value in fishing is particularly associated with fishers embodied cultural capital [18].…”
Section: The 'Goodfisher'mentioning
confidence: 99%
See 3 more Smart Citations